2020
DOI: 10.1074/jbc.ra120.012809
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis (Mtb) lipid mediated lysosomal rewiring in infected macrophages modulates intracellular Mtb trafficking and survival

Abstract: Intracellular pathogens commonly manipulate the host lysosomal system for their survival. However, whether this pathogen-induced alteration affects the organization and functioning of the lysosomal system itself is not known. Here, using in vitro and in vivo infections and quantitative image analysis, we show that the lysosomal content and activity are globally elevated in Mycobacterium tuberculosis (Mtb Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 88 publications
(119 reference statements)
2
28
0
Order By: Relevance
“…The data on differential trafficking of Mtb to lysosomes in cells with high vs low endocytic capacities in the same population corroborates our previous result that lysosomal content could influence the trafficking of Mtb 22,32 . While these correlations need to be better understood in detailed mechanistic terms, our data showing differential trafficking of Mtb to lysosomes in distinct subsets of cells in a non‐perturbed macrophage population identifies endocytic capacity as a crucial determinant of phagocytic uptake as well as downstream trafficking.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The data on differential trafficking of Mtb to lysosomes in cells with high vs low endocytic capacities in the same population corroborates our previous result that lysosomal content could influence the trafficking of Mtb 22,32 . While these correlations need to be better understood in detailed mechanistic terms, our data showing differential trafficking of Mtb to lysosomes in distinct subsets of cells in a non‐perturbed macrophage population identifies endocytic capacity as a crucial determinant of phagocytic uptake as well as downstream trafficking.…”
Section: Discussionsupporting
confidence: 89%
“…At a population level, the proportion of Mtb delivered to lysosomes is thus an average of these two bins. Our previous results suggested that the lysosomal content of the cell influences Mtb trafficking 22,32 . Hence, we assessed if the total lysosomal content of cells co‐varies with endocytic capacity in the two bins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages are thought to exhibit different levels of antimicrobial activities depending on the nature of stimuli, but the pattern of difference is not consistent between different in vitro macrophage models (Yates et al, 2005;Podinovskaia et al, 2013;Sachdeva et al, 2020). For example, in mouse bone marrow-derived macrophages (BMDM) phagocytosis of Mycobacterium tuberculosis (Mtb) results in a higher proteolytic activity than phagocytosis of non-immunogenic IgG, but the induced acidification activity is at a similar level (Podinovskaia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%